Gold Nanorods as Visual Sensing Platform for Chiral Recognition with Naked Eyes - Wang, Yanwei (Sci Rep, 2018)
Chirality plays a key role in modern science and technology. Here, we report a simple and effective sensing platform for visual chiral recognition of enantiomers. In this sensing platform, gold nanorods (AuNRs) prepared through a common synthesis route are used as colorimetric probes for visual recognition of glutamine (Gln) enantiomers. D-Gln could rapidly induce the aggregation of AuNRs, thereby resulting in appreciable blue-to-gray color change of AuNRs solution; however, L-Gln could not induce color change of AuNRs. This distinct color change can be easily distinguished by the naked eyes; as a result, a visual method of chiral recognition was suggested. The method was applied to determine the enantiometric excess of D-Gln through the whole range of −100% ~ 100%. The chiral assay can be performed with a simple UV-vis spectrometer or the naked eyes. Notably, the AuNRs do not need any chiral labeling or modification, and the chiral recognition is based on the inherent chirality of AuNRs. This chiral assay method is simple, sensitive, cheap and easy to operate. This study is the first example using AuNRs for direct visual recognition of enantiomers, and will open new opportunity to construct more chiral recognition methods for some important compounds.